Sportowe wpisy motywacyjne jako element współczesnego komunikowania społecznego (na przykładzie postów Ewy Chodakowskiej) = Sport-related motivational entries as an element of contemporary social communication (based on Ewa Chodakowska`s posts) - Klimek, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Motivational entries make a perfect material not only for linguistic but also psychological and sociological research. In the literature on the subject no attempt has so far been made to define motivational entries, examine their composition or determine the role they play in contemporary communication.
Keywords: wpis motywacyjny; komunikacja społeczna; perswazja; sport; Chodakowska, Ewa (1982- ); motivational entries; social communication; persuasion